Improving the Estimation of Hydraulic and Thermal Properties of Heterogeneous Media via the Addition of Heat Loss - Pan, M. (2020)
The measured temperature of the sand layer was used to estimate the hydraulic conductivities and longitudinal and transverse thermal dispersivities via curve fitting using HYDRUS software. We found that >50% of the sensible heat was dissipated into the shell of sandbox and the surrounding air rather than being absorbed by the sand. Two methods were then proposed to quantify the heat loss and to improve the accuracy of parameter estimation: (i) a conceptual heat balance method that accounted for the change in heat storage in different parts of the system and (ii) a physical process‐based method that described the thermodynamic processes of heat transfer among different parts of the system. On combining these two methods, the relative error between the estimated and measured water flux significantly decreased from 19% to nearly 2%. The results imply that the heat‐tracing method is capable of obtaining accurate hydraulic and thermal properties in a heterogeneous porous medium with the addition of heat loss.